Proceedings of the 8th Workshop on Workflows in Support of Large-Scale Science 2013
DOI: 10.1145/2534248.2534253
|View full text |Cite
|
Sign up to set email alerts
|

Execution time prediction for grid infrastructures based on runtime provenance data

Abstract: An accurate performance prediction service can be very useful for resource management and the scheduler service and help them make better resource utilization decisions by providing better execution time estimates. In this paper we present a novel approach of predicting the execution time of computational tasks for Grid infrastructures using machine learning models based on multilayer perceptron combined with a principal feature selection algorithm for selecting the most important runtime features.Our techniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…It would be interesting to uncover hidden patterns or draw new insights by applying data mining techniques on provenance data. So far, a rich body of existing literature has focused on (i) exploring a workflow pattern that frequently appears [13][14][15], (ii) applying provenance data to scheduling or optimizing simulations and workflows that are in execution [16][17][18], and (iii) estimating when to complete a specified workflow (or simulation) [19,20]. Recently, there has been a growing need to apply a variety of data mining techniques to develop frequent pattern mining and classification to provenance data.…”
Section: Advanced Utilization Of Simulation Provenancementioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to uncover hidden patterns or draw new insights by applying data mining techniques on provenance data. So far, a rich body of existing literature has focused on (i) exploring a workflow pattern that frequently appears [13][14][15], (ii) applying provenance data to scheduling or optimizing simulations and workflows that are in execution [16][17][18], and (iii) estimating when to complete a specified workflow (or simulation) [19,20]. Recently, there has been a growing need to apply a variety of data mining techniques to develop frequent pattern mining and classification to provenance data.…”
Section: Advanced Utilization Of Simulation Provenancementioning
confidence: 99%
“…Malik's group [19] suggested a method of predicting the execution time of a computing job on Grid infrastructures, via machine learning methods. For model training, they utilized provenance data in association with job execution.…”
Section: Execution Performance Predictionmentioning
confidence: 99%
“…The problem of learning cost estimators has been addressed in the recent past, but mainly for specific scenarios that are relevant to data analytics, namely workflow-based programming on clouds and grid [24,25]. But for instance [26] showed that runtime, especially in the case of machine learning algorithms, may depend on features that are specific to the input, and thus not easy to learn.…”
Section: Estimation Impact and Cost Of Refreshmentioning
confidence: 99%
“…Learning cost estimators. This problem has been addressed in the recent past, but mainly for specific scenarios that are relevant to data analytics, namely workflow-based programming on clouds and grid, [17,12]. But for instance [14] showed that runtime, especially in the case of machine learning algorithms, may depend on features that are specific to the input, and thus not easy to learn.…”
Section: Process Management Challengesmentioning
confidence: 99%